The price of rights : regulating international labor migration - Ruhs, Martin (Princeton University Press, 2013)
Many low-income countries and development organizations are calling for greater liberalization of labor immigration policies in high-income countries. At the same time, human rights organizations and migrant rights advocates demand more equal rights for migrant workers. The Price of Rights shows why you cannot always have both. Examining labor immigration policies in over forty countries, as well as policy drivers in major migrant-receiving and migrant-sending states, Martin Ruhs finds that there are trade-offs in the policies of high-income countries between openness to admitting migrant workers and some of the rights granted to migrants after admission.